Effect of Precipitation on Air Pollutant Concentration in Seoul, Korea - Kim, Suhyang; Hong, Ki-Ho; Jun, Hwandon; Park, Young-Jae; Park, Moojong; Sunwoo, Young (Asian journal of atmospheric environment (Online), 2014)
In this study, long-term rainfall data with irregular spatial distribution in Seoul, Korea, were separated into individual precipitation events by the inter-event time definition of 6 hours. Precipitation washout of PM 10 and NO 2 concentrations in the air considering various complex factors were analyzed quantitatively. Concentrations of PM 10 and NO 2 in the atmosphere were lower under condition of rainfall compared to that of non-precipitation, and a noticeable difference in average PM 10 concentrations was observed. The reduction of concentrations of PM 10 and NO 2 by rainfall monitored at road-side air monitoring sites was also lower than that of urban air monitoring sites due to continuous pollutant emissions by transportation sources. Meanwhile, a relatively smaller reduction of average PM 10 concentration in the atmosphere was observed under conditions of light rainfall below 1 mm, presumably because the impact of pollutant emission was higher than that of precipitation scavenging effect, whereas an obvious reduction of pollutants was shown under conditions of rainfall greater than 1 mm. A log-shaped regression equation was most suitable for the expression of pollutant reduction by precipitation amount. In urban areas, a lower correlation between precipitation and reduction of NO 2 concentration was also observed due to the mobile emission effect.